Quantitative Analysis and Evaluation of Tractor Gear Shifting Comfort with Entropy-Based Matter-Element Model - Jiang, Wei; Xu, Hongmei; Zhong, Wenjie; Dong, Jiajun; Shang, Yujun (Recent Advances in Computer Science and Communications, 2021)
Background: The gear shifting comfort of tractors is affected by various factors, which make it extremely difficult to accurately and quantitatively describe the handling comfort through objective physical quantities. However, the calculation and evaluation processes of the index of manipulation comfort mostly involve the operation of matrix form, and the numerical operation is one of the powerful core functions of MATLAB. Objective: This study aims to take the gear shifting process of tractors as the research object and uses MATLAB /GUI toolbox to develop the shifting comfort evaluation system, thereby improving the gear shifting comfort. Methods: The procedures of holistic assessment, element subdivision, and detailed tracking were adopted as the analysis method. Thus, the operation process was divided into four action units, including pedal free travel, separation travel, gear change, and joint travel, according to the concept of “differentiation” and manipulation behavior. Based on the matter-element model, the process of clutch operation was described by the coupling of action elements. The closeness between the actual model and the target model was used to measure the degree of handling comfort. Then, the results were compared with those of the multi-index comprehensive evaluation. Results: It was shown that separation travel has the greatest influence on handling comfort. Taking vehicle 1 as an example, the matter-element analysis model provided the overall comfort value of the carrier (0.8359), which is close to the value of the multi-index comprehensive evaluation (0.8156). Moreover, the evaluation results presented the score of each action unit, which could directly reflect the action units with the lowest level of comfort. The evaluation results of matterelement model can not only reflect the handling comfort of different components, but also locate the negative aspects of the whole operation. Conclusion: This method is effective in overcoming the ambiguity of the concept of comfort and the generality of overall evaluation as well as avoiding the uncertainty of subjective evaluation.
Keywords: evaluation system